Best Prognostic Indicator For Sarcoidosis - Kirkil, G.; Baughman, R. P.; Lower, E. E. (Amer Thoracic Soc, 2017)
[Abstract Not Available]
International Conference of the American-Thoracic-Society (ATS) -- MAY 19-24, 2017 -- Washington, DC